Pengembangan Penilaian Instrumen Otentik Pada Praktikum Pembuatan Larutan Untuk Mahasiswa Pendidikan Kimia - Ino Talino; Masriani Masriani; Lukman Hadi (Peneliti.net, 2022)
Abstract This study aims to determine the feasibility and response of the practicum assistant to the authentic assessment instrument in the practicum of making basic chemistry solutions at the Chemistry Education FKIP of Tanjungpura University. The form of this research is research and development (R&D) which adopts the Jerrold E. Kemp development model. The subject of this study was an authentic assessment instrument in the laboratory for making basic chemistry solutions that were tested on 20 lab assistants at the Chemistry Education FKIP of Tanjungpura University. The data collection instruments used was the feasibility assessment sheet and the practicum assistant questionnaire. The results of data processing indicate that the authentic assessment instrument developed is very feasible by seeing the results of the content validity with a value of one in terms of material and language aspects. Based on the calculation results of the practicum assistant questionnaire response to the authentic assessment instrument that was developed is very well (85.90%). This shows that the feasibility assessment and the response of the practicum assistant to the authentic assessment instrument are very suitable for use in the practicum process. Keywords: Authentic Assessment Instrument, Practical Assessment of Solution Making